Prevalence and clinical significance of systolic impairment in hypertrophic cardiomyopathy. Issue 7 (14th June 2005) - Thaman, R; Gimeno, J R; Murphy, R T; Kubo, T; Sachdev, B; Mogensen, J; Elliott, P M; McKenna, W J
Abstract : Objectives: To determine the frequency of systolic impairment (SI) and its impact on the natural history of hypertrophic cardiomyopathy (HCM). Methods: 1080 patients (mean (SD) age 43 (15) years, 660 men) with HCM were evaluated. Initial assessment included history, examination, 48 hour Holter monitoring, cardiopulmonary exercise testing, and echocardiography; SI was defined as a fractional shortening (FS) ⩽ 25%. Survival data were collected at clinic visits or by direct communication with patients and their general practitioners. The results of serial echocardiography in 462 patients with normal FS at presentation are also reported. Results: 26 (2.4%) patients (49 (14) years, 18 men) had SI at the initial visit. During follow up (58 (49) months), nine (34.6%) died or underwent cardiac transplantation compared with 108 (10.2%) patients with normal FS (p = 0.01). Five year survival from death (any cause) or transplantation was 90.1% (95% confidence interval (CI) 87.8 to 92.4) in patients with normal systolic function versus 52.4% (95% CI 25.2 to 79.6, p < 0.0001) in patients with SI. In patients who underwent serial echocardiography, 22 (4.8%, aged 41 (15) years) developed SI over 66 (40) months; the annual incidence of SI was 0.87% (95% CI 0.54 to 1.31). On initial evaluation patients who developed SI had a higher frequency of syncope (67 (15.2%) v 10 (45.5%) of those who did not develop SI, p = 0.001), non-sustained ventricular tachycardia (91 (20.6%) v 11 (50%), p = 0.002), and an abnormal blood pressure response on exercise (131 (29.7%) v 15 (68.2%), p = 0.001). Patients with SI had greater wall thinning (p = 0.001), left ventricular cavity enlargement (p < 0.0005), and deterioration in New York Heart Association functional class (p = 0.001) during follow up. Thirteen (59.1%) patients who progressed to SI died or underwent transplantation compared with 38 (8.6%) patients who maintained normal systolic function. Conclusions: SI is an infrequent complication of HCM but, when present, is associated with a poor prognosis.